Empowering Women to Occupy Leadership Positions - عبد المنعم علي نجرس هبة عبد المحسن عبد الكريم (College of Education for Women, 2019)
In this research , we tried to identify the meaning empowerment in the development literatures , and inquire the most enabling prominent actions to promote women , as we considered the most important international conferences that take up the subject of women's empowerment . In the context of research on the subject of empowering women to occupy leadership positions , we tried to diagnose the target of the empowerment , and we clarify the correlation between human development and empowerment of women , also the research touched on the decision (1325) issued by the United Nations , which includes provisions regarding the importance of women participation at all levels in the process of decision-making . We realized that there are social , cultural and political challenges and stereotypes molds crisis encapsulating the reality of women in Iraq . So , she needs enable that moves toward the psychological inside to improve her perceptions about herself , and another external that moves towards improving the society perceptions about her. We have reached a number of recommendations and proposals to change the reality of women to reach a better and brighter reality by the means of education , and raise society awareness of the importance of women's status and her role in society , and instill self-confidence of women in order to be conscious of her rights and have ability to claim those rights .